Observational Study of Animal-Based Physical Exercise Programs for Improving Fundamental Movement Skills in Toddlers - Vina Firmanty Mustofa; Nidya Comdeca Nurvitriana; Resinta Rahma Mareta Saputri; Anindya Aurellia Ardianto Putri; Shiva Ajeng Prihandoko; Rahmadania Tri Widiasari (Journal of Research in Midwifery and Healthcare, 2026)
Early childhood is a critical period for the development of fundamental movement skills (FMS). However, Indonesia continues to face challenges related to motor development, with motor delays affecting approximately 29.9% of children. This study aimed to develop an Animal-Based Physical Exercise program designed to support FMS development in toddlers through a simple, contextual, and enjoyable approach. This study employed a descriptive observational design with a limited pilot implementation. The study involved seven toddlers aged 2-5 years and two instructors at a fitness studio in Surabaya. Data were collected through direct observation of physical exercise activities and brief interviews with the instructors. The observation findings were used to develop the Animal-Based Physical Exercise program, which was subsequently implemented on a limited basis with two toddlers aged 1.5 and 4 years. The collected data were analyzed descriptively by organizing and interpreting the observation and implementation findings. The observations showed that younger children required more guidance and participated less consistently during the activities, whereas the older child was able to follow the movement sequence more independently and participated actively throughout the session. These observations suggest that children's responses to physical exercise may vary according to their developmental stage. The developed Animal-Based Physical Exercise program integrates animal imitation movements into structured play activities to encourage locomotor skills, balance, coordination, and active participation. This study provides a practical and contextually appropriate physical exercise program that can be implemented in fitness studios, early childhood education settings, and at home to support toddlers' motor development. The findings also provide preliminary information for developing age-appropriate physical activity programs and may serve as a reference for future studies involving larger samples and longer implementation periods.